2021
DOI: 10.1016/j.jns.2021.117486
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of long-term outcomes among hospitalized COVID-19 patients with and without neurological complications

Abstract: Background Little is known regarding long-term outcomes of patients hospitalized with COVID-19. Methods We conducted a prospective study of 6-month outcomes of hospitalized COVID-19 patients. Patients with new neurological complications during hospitalization who survived were propensity score-matched to COVID-19 survivors without neurological complications hospitalized during the same period. The primary 6-month outcome was multivariable ordinal analysis of the modifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
182
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 164 publications
(200 citation statements)
references
References 38 publications
12
182
2
4
Order By: Relevance
“…Nevertheless, our understanding of the long-term implications is limited. It has been shown that patients previously hospitalized with COVID-19 display a wide array of neurological symptoms months after discharge (10,12,37) but few studies have systematically followed patients over time, likely because of the inherent difficulties in doing so. However, based on our present data, we posit that longitudinal measurements of serum NFL would provide an efficient means to identify and quantify neurological injury in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, our understanding of the long-term implications is limited. It has been shown that patients previously hospitalized with COVID-19 display a wide array of neurological symptoms months after discharge (10,12,37) but few studies have systematically followed patients over time, likely because of the inherent difficulties in doing so. However, based on our present data, we posit that longitudinal measurements of serum NFL would provide an efficient means to identify and quantify neurological injury in hospitalized patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Although common symptoms of coronavirus disease 2019 (COVID-19) include fever, cough, fatigue and shortness of breath, the manifestations of COVID-19 can vary widely. For example, some patients can develop pneumonia, acute respiratory distress syndrome, myocardial injury, arrhythmias and/or multi-organ failure (2), and it is increasingly recognized that SARS-CoV-2 can cause neurologic signs (3)(4)(5)(6)(7)(8)(9)(10). Indeed, clinical studies observed neuropsychiatric manifestations in up to 70% of patients with COVID-19, including young adults and patients in whom respiratory symptoms have long resolved (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontera et al [6] conducted a prospective study where they followed 382 patients who developed neurological complications during the acute phase of COVID-19 for 6 months, observing that 91% at least persisted with 1 abnormal outcome, 56% had limitations in performing activities of daily living, 50% had cognitive impairment, 47% were unable to return to work, and 62% scored worse than average on ≥ 1 Neuro-QoL scale (worse anxiety 46%, sleep 38%, fatigue 36%, and depression 25%) [6] . The authors concluded that those who present any type of neurological complication during the acute phase of COVID-19 have a worse prognosis at 6 months compared to those who do not.…”
mentioning
confidence: 99%
“…The authors concluded that those who present any type of neurological complication during the acute phase of COVID-19 have a worse prognosis at 6 months compared to those who do not. However, it is observable that almost all of those who present neurological manifestations persist in the long term [6] . Therefore, it is expected that the prognosis in those with a history of neuropsychiatric disorders will be worse [4] .…”
mentioning
confidence: 99%